Effectiveness of Group Guidance and Discussion Techniques and Its Effect on Level Social Interaction of Mosque Youth - Rahmad, Rahmad (PT. Riset Press International, 2023)
This article explains the effectiveness of group guidance and discussion techniques and their influence on the level of social interaction among mosque youth.As social beings in the community, teenagers always carry out a process of social interaction with fellow individuals and other groups in community life. However, the ability to interact among adolescents is still low and some even have difficulty adjusting to social interactions. This research is a quantitative study using the pre-experimental design method, type one group pretest-posttest (preliminary test, final test of a single group). The total population was 12 mosque teenagers, because this research was conducted on teenagers from the Nurul Iman Pasirpengaraian mosque. Data were collected using questionnaires and observations and using a total item correlation limit of rix 0.25 as the item selection criterion. Assessment analysis can be obtained from the results of calculating pretest and posttest scores. The acquisition of pretest and posttest scores is carried out in several stages. The initial stage is the pretest activity, and the final stage is the posttest activity. The results of this study indicate that the level of social interaction among adolescents at the Nurul Iman mosque, before being given treatment, is still classified as in the low category which is in the interval range 47 to 56. Then it has increased from 47.58 to 79.25, which means that group guidance and discussion techniques have an effect on adolescent social interactions.